2021
DOI: 10.1371/journal.pone.0238210
|View full text |Cite
|
Sign up to set email alerts
|

Retention of lumpy skin disease virus in Stomoxys spp (Stomoxys calcitrans, Stomoxys sitiens, Stomoxys indica) following intrathoracic inoculation, Diptera: Muscidae

Abstract: Lumpy skin disease (LSD) is an emerging disease of cattle in Kazakhstan and the means of transmission remains uncertain. In the current study, retention of Lumpy Skin Disease Virus (LSDV) by three Stomoxys species following intrathoracic inoculation was demonstrated under laboratory conditions. A virulent LSDV strain was injected into the thorax of flies to bypass the midgut barrier. The fate of the pathogen in the hemolymph of the flies was examined using PCR and virus isolation tests. LSDV was isolated from … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 22 publications
(8 reference statements)
2
14
0
Order By: Relevance
“…One animal that was inoculated with the lowest dose displayed a delayed onset of clinical signs (19 dpi) compared to other cattle in the study (7-9 dpi) (57). The incubation period of 11-12 dpi seen in our study in the RS and RA groups is consistent with previous studies which reported incubation periods following arthropod inoculation of LSDV of 12-26 dpi (19), and 10-14 dpi (20). This data suggests that the incubation period of LSD in the field is longer than the 5-7 days reported in experimental studies using needle inoculation, and more likely to be 10-14 days and possibly longer.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…One animal that was inoculated with the lowest dose displayed a delayed onset of clinical signs (19 dpi) compared to other cattle in the study (7-9 dpi) (57). The incubation period of 11-12 dpi seen in our study in the RS and RA groups is consistent with previous studies which reported incubation periods following arthropod inoculation of LSDV of 12-26 dpi (19), and 10-14 dpi (20). This data suggests that the incubation period of LSD in the field is longer than the 5-7 days reported in experimental studies using needle inoculation, and more likely to be 10-14 days and possibly longer.…”
Section: Discussionsupporting
confidence: 92%
“…The pathology is focused on the skin as a multifocal dermatitis with vasculitis of dermal blood vessels, resulting in full-thickness necrosis of the dermis and epidermis (11). Unusually for a poxvirus, direct transmission of LSDV is rarely documented however LSDV can be transmitted by hematophagous arthropods including Aedes aegypti mosquitoes, Rhipicephalus microplus ticks and Stomoxys calcitrans stable flies (14,(16)(17)(18)(19)(20). The main methods for the control and prevention of LSDV are effective surveillance programmes to detect outbreaks, widespread use of live attenuated vaccines, and 'stamping out' of infected herds (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are supported by experimental work which has shown that LSDV can be transmitted from clinical donor to naive recipient via Aedes aegypti ( 7 ), Haematopota spp. horse flies ( 14 ), and the biting flies Stomoxys calcitrans , Stomoxys sitiens , and Stomoxys indica ( 14 , 15 ). Experimental transmission of LSDV (but not the disease) has also been demonstrated via Rhipicephalus appendiculatus ticks ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Two recent experimental studies demonstrated that S. calcitrans biting flies and Haematopota spp. horseflies (Sohier et al., 2019) and Stomoxys species; Stomoxys calsitrans , Stomoxys sitiens , Stomoxys indica can mechanically transmit LSDV to cattle (Issimov et al., 2021). Overall, Stomoxys flies are considered by far as the most plausible vectors of LSD.…”
Section: Introductionmentioning
confidence: 99%